A Novel 1×2 Thermo-Optic Multimode Interference Switch Structure Based on Photodefinable Benzocyclobutene (BCB 4024-40) Polymer on Silica - Ibrahim, Mohd. Haniff; Chin, Mee Koy; Mohd. Kassim, Norazan; Mohammad, Abu Bakar (Chinese Physical Society, 2006)
A novel 1×2 multimode interference photonics switch structure based on thermal controlling effect is proposed. A ridge waveguide of photosensitive polymer, benzocyclobutene (BCB 4024-40) on silica clad is used as a design structure. A temperature changes as a result of electrode heating are analysed by employing a two-dimensional finite difference thermal model considering both conduction and convection mechanisms. The switching characteristics due to changes in effective index are analysed by the two-dimensional finite difference beam propagation method with transparent boundary condition. The proposed structure works well with low crosstalk level of -28 dB and low switching power relatively to the structural upper cladding thickness.